(3eHGMK GdJaSjQs - (3CHh MGeO CMeO Hf eMeO Hf GdeXaQ Hf GdeNJGQ GdQGRjs
(3ChdgG (B:s
(3bGd GHh GSMb GdKYGdHi QMeg Gddg s
(3BNQgG (B:s
(3bGd hHVGYI GdeGd hcKQI GdSDGd , MOjK UMjM s
(3edhKI ef GdMhGas
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3ceGd GdOjf CHj GdaVGFds
Keywords: (3GdJaSjQ hYdhe GdbQBfs